The Modified Sublay Technique for the Management of Major Subcostal Incisional Hernia: Long-Term Follow-up Results of 37 Consecutive Patients. Issue 2 (25th February 2022) - Zuvela, Marinko; Galun, Danijel; Bogdanovic, Aleksandar; Bidzic, Nemanja; Zivanovic, Marko; Zuvela, Milos; Zuvela, Milan
Abstract : Background: The aims of this study were to present the concept of original technique in the management of major incisional subcostal hernias and to evaluate short- and long-term outcome. Method: Between January 2010 and January 2020, 280 patients underwent hernia repair surgery for incisional lateral abdominal hernia at Clinic for Digestive Surgery, Clinical Center of Serbia. Among them, 37 patients underwent the modified sublay technique for major incisional subcostal hernia with minimal hernia defect surface of 100 cm 2 or greater or minimal hernia defect width or height of 10 cm or greater. The operative techniques are as follows: retromuscular dissection of rectus muscle from posterior sheath on the both sides of hernia defect, external oblique muscle dissection from internal oblique muscle in a circle around hernia defect at the side of the hernia defect, complete reconstruction of the posterior myofascial layer, large heavyweight polypropylene mesh placement in a sublay position, and complete or partial reconstruction of anterior myofascial layer. Results: A median (range) hernia defect surface was 150 (100–500) cm 2 . A median operative time was 130 (90–330) minutes. The morbidity rate was 18.9%. A median (range) postoperative hospital stay was 7 (2–24) days. After the median follow-up of 50 (1–108) months, 2 patients (5.4%) developed recurrent hernia. Conclusions: The modified sublay technique using large heavyweight polypropylene mesh provides good results in the management of major subcostal abdominal wall defects.